PRODUCTION OF HIGH QUALITY SILAGE FROM COARSE STERM FORAGE WITH THE USE OF LACTIC ACID AND PROPIONATE CULTURES - Balpanov , D.S.; Ten , О.А.; Essepbay , G.E.; Barbasova , S.K. (Eurasian Journal of Applied Biotechnology, 2014)
In modern economic environment practical production of fodder in our country doesn’t have sufficient range of affordable, cheap and efficient domestic preserving additives and mixtures to improve the conditions of ensiling green mass of plants, as well as the composition and quality of the prepared silage. The reason of the study is to obtain high-quality silage from the straw, the basis of the research are the strain of lactic acid culture Lactobacillus plantarum F-1 and the strain of propionic culture Propionibacterium acidopropioni F-5, because silage prepared together with lactic acid and propionic acid bacteria is of high quality. To achieve the goal of the research, the following work has been carried out: The modes of cultivation of lactic culture Lactobacillus plantarum F-1 and propionic culture Propionibacterium acidopropioni F-5 have been selected. Optimal mode of concentration has been selected. The optimal mode of drying of biomass of lactic acid culture Lactobacillus plantarum F-1 and propionic culture Propionibacterium acidopropioni F-5 in semiindustrial conditions has been selected. The optimal ratio of dry biomass of bacteria in the silage ferment has been selected.